Phosphatidylinositol 3‐Phosphate Mimics Based on a Sulfoquinovose Scaffold: Synthesis and Evaluation as Protein Kinase B Inhibitors1. Issue 27 (27th August 2014) - Gabrielli, Luca; Calloni, Ilaria; Donvito, Giulia; Costa, Barbara; Arrighetti, Noemi; Perego, Paola; Colombo, Diego; Ronchetti, Fiamma; Nicotra, Francesco; Cipolla, Laura
Abstract: New sulfoquinovose analogues of phosphatidylinositol 3‐phosphate have been synthesised based on a sulfoquinovose scaffold as potential protein kinase B (PKB) inhibitors. The synthetic strategy involved the introduction into glucose of a thioacetate group at the 6‐position and of an azide group at the anomeric position as precursors of the sulfonate and phosphoramidate moieties present in the final compounds. The synthesised compounds were tested in vitro on isolated PKB by means of ELISA assays and for their anti‐proliferative activity against the human ovarian carcinoma cell line IGROV‐1. Sulfoquinovose derivatives2b and2c showed inhibitory activity in the low micromolar range. Abstract : Novel protein kinase B inhibitors have been designed as phosphatidylinositol 3‐phosphate mimics and synthesised by using a 6‐deoxy‐6‐sulfoglucose scaffold.